The relationship between social advertising and consumer purchase intention - Ahmad Syakir bin Kadimin1, Ahmad Syakir bin Kadimin1; Adam , Adi Jaya; Md Yusuf , Mohd Sahrir (Jurnal Penyelidikan Sains Sosial, 2025)
Businesses set a high priority on incorporating social media advertising into their plans since it influences consumers' purchasing decisions and helps increase brand awareness. The study aims to investigate the relationship between social media advertising and online purchase intention in Bintulu, Sarawak. In this quantitative study, 300 participants who were accustomed to using social media and online purchasing were given self-administered questions. The study assessed the importance and dependability of the data gathered using statistical analytic techniques. The findings showed that customers' intentions to make online purchases are significantly and favourably impacted by both celebrity endorsement and interactivity. Celebrity endorsement increases credibility and helps build a positive brand image that meets consumer expectations, while interactivity encourages active user participation and strengthens trust and emotional connections with businesses. Moreover, this research contributes to the growing body of literature on digital marketing by providing localized empirical evidence from a semi-urban Malaysian context. By highlighting the strategic significance of creating interactive, tailored, and influencer-supported ads to impact customer behaviour, the study adds insightful information to the field of digital marketing. The results can help practitioners create social media strategies that are more successful and meet changing customer demands. Several suggestions are made considering the research results to help businesses understand that social media advertising may boost sales.